The Influence of Religiosity, Organizational Culture, and Islamic Leadership Style on the Performance of Management of Student Organizations at the Faculty of Economics and Business, Muhammadiyah University, Surakarta - Adyansyah, Wafiyuddin; Waskito, Jati; Cahyo, Ilham Nur (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
This study aims to analyze and determine the effect of the level of religiosity, organizational culture, and Islamic leadership style on the performance of student organization officials at the Faculty of Economics and Business, Muhammadiyah University, Surakarta. The independent variables in this study are religiosity, organizational culture, and Islamic leadership style. The performance of student organization officials is the dependent variable. This type of research is quantitative research, with a population of student organization management groups at the Faculty of Economics and Business, Muhammadiyah University of Surakarta. Samples were taken randomly with a minimum number of respondents of 100 students from all student organization administrators at the Faculty of Economics and Business, Muhammadiyah University of Surakarta. The sampling technique uses the theory of Hair which says that the minimum number of samples is 5 times the number of variables to be studied and analyzed. For analysis in this study using multiple linear regression analysis and data collection techniques through the distribution of questionnaires conducted online via Googleform. Based on the results of data processing assisted by the SPSS software, the results of the study were obtained through the t test, with the result that the religiosity variable had a positive and significant effect on the performance of the student organization committee of the Faculty of Economics and Business, Muhammadiyah University of Surakarta. Organizational culture variables have a positive and significant impact on the performance of student organization management at the Faculty of Economics and Business, Muhammadiyah University of Surakarta. As well as the Islamic leadership style variable does not have a positive and significant effect on the performance of student organization management at the Faculty of Economics and Business, Muhammadiyah University of Surakarta.